Approach to the general features of neutral Spanish - Crego, Vicky (2025)
Just as the definition of neutral Spanish (also known as global, international or Latin) involved continuous controversy in the linguistic community, specifying the features that individualize it constitutes the next phase in which attempts are made to outline, with greater or lesser precision and depth, the characteristics that individualize it, and that also justify its existence and real need. In this paper we intend to focus on the general features that form the basis of neutral Spanish, particularly at the phonic, grammatical and lexical levels. For this purpose, we will resort to different works that deal with this subject, with the aim of establishing tables that synthesize the main lines of the linguistic skeleton of the variant under study, a skeleton susceptible to evolution, modification or change by virtue of the external conditioning factors that sustain and determine it. Finally, we will briefly deal with some manuals or guides that the different audiovisual and translation companies provide as a guiding light for the human assets at their disposal.